2003
DOI: 10.1002/jctb.869
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polyacrylamide‐co‐acrylic acid on cellulose production by Acetobacter xylinum

Abstract: Polyacrylamide-co-acrylic acid (PA) added to shake flask cultures of Acetobacter xylinum at concentrations up to 3 g dm −3 resulted in increased production of bacterial cellulose. For PA concentrations of 0-3 g dm −3 , 7-day cellulose production rose monotonically from 2.7 ± 0.8 to 6.5 ± 0.5 g dm −3 at a shaker speed of 175 rpm, and from 1.7 ± 0.01 to 3.7 ± 0.5 g dm −3 at shaker speed of 375 rpm. Addition of PA also changed the morphology of the biomass from amorphous/stringy forms to spheroidal particles with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…Joseph et al [10] reported that 7-day BC production by A.xylinum BPR2001 rose from 2.7 to 6.5 g/l at a shake speed of 175 rpm and from 1.7 to 3.7 g/l at shake speed of 375 rpm at PCA concentrations of 0-0.3%. In the shake Xask experiments, a signiWcant increase in BC production was also attained by the addition of NaAlg, a water-soluble polysaccharide in our research.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Joseph et al [10] reported that 7-day BC production by A.xylinum BPR2001 rose from 2.7 to 6.5 g/l at a shake speed of 175 rpm and from 1.7 to 3.7 g/l at shake speed of 375 rpm at PCA concentrations of 0-0.3%. In the shake Xask experiments, a signiWcant increase in BC production was also attained by the addition of NaAlg, a water-soluble polysaccharide in our research.…”
Section: Discussionmentioning
confidence: 98%
“…Recently there are a few reports stating that addition of water-soluble polymers such as xanthan, agar, polyacrylamide-co-acylic acid (PCA), and acetan can increase relative viscosity of the broth to reduce shear stress, hinder coagulation of BC during the cultivation to form uniform smaller pellets, which are advantageous to transfer nutrients and oxygen into bacterial cells located inside and on the surface of the cellulose matrix, and further promote BC productivity into the medium, will assist in enhancing BC productivity [1,3,9,10]. On the other hand, various watersoluble polymers added into the medium are known to interfere with the aggregation of microWbrils into a normal ribbon assembly, aVect the crystallization of cellulose I and I and introduce the characteristic properties of these additives to attain BC composite materials [6].…”
Section: Introductionmentioning
confidence: 99%
“…High production of BC has been achieved using fructose as a carbon source (Joseph, Rowe, Margaritis, & Wan, 2003). More recently, unconventional feedstocks from renewable resources and waste streams have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations showed that the higher shear caused by the impeller in the stirred tank bioreactor produces a negative effect on BC production, which decreases increasing stirring speed. 28,41 The CSL seems to have a negative impact on BC production in the airlift bioreactor as the CSL-fructose medium gave a productivity of 0.119 g L −1 h −1 . This is 75.7% less than the case when CSL was not used (i.e.…”
Section: Effect Of the Type Of Reactor On Productionmentioning
confidence: 98%
“…Joseph et al 41 studied the shake flask cultures with added polyacrylamide-co-acrylic acid using Acetobacter xylinum BPR2001 (ATCC No 700178). An increase in the production of BC was observed.…”
Section: Effect Of the Type Of Reactor On Productionmentioning
confidence: 99%